Taxonomic notes on the Australian skyhopper genus Kosciuscola Sjöstedt (Orthoptera: Acrididae: Oxyinae) - Song, Hojun; Muschett, Giselle R.; Woller, Derek A.; Slatyer, Rachel A.; Tatarnic, Nikolai J.; Umbers, Kate D. L. (Zootaxa, 2021)
The Australian skyhopper genus Kosciuscola Sjöstedt consists of brachypterous species that inhabit the Australian alpine and subalpine region. The genus used to include 5 species and 1 subspecies, but according to a recent phylogenomic study, there could be as many as 14 species in the genus, that are genetically and geographically isolated from each other. This study represents the first step in describing and documenting the diversity of this interesting genus. In this study, we redefine the type species K. tristis, and elevate its subspecies K. tristis restrictus as a valid species on the basis of distinct morphological traits, geographical isolation, and phylogenomic evidence.